Predicting the Adult Clinical and Academic Outcomes in Boys With ADHD: A 7- to 10-Year Follow-Up Study in China - Ren, Yanling; Fang, Xinyu; Fang, Hui; Pang, Gaofeng; Cai, Jing; Wang, Suhong; Ke, Xiaoyan (Frontiers in Pediatrics, 2021)
Background: Attention-deficit/hyperactivity disorder (ADHD) often persists into adulthood and causes adverse effects on social functioning. The present study aimed to widely investigate the predictors, particularly childhood intelligence quotient (IQ) and family environment factors, on adult clinical and academic outcomes in boys with ADHD. Methods: A total of 101 boys with ADHD in a Chinese Han ADHD cohort were followed up 7 to 10 years later. Baseline ADHD symptoms were evaluated using the parent version of the ADHD Rating Scale‐IV (ADHD‐RS‐IV) and the Chinese version of the Conners’ Parent Rating Scale-Revised (CPRS-48). The intelligence of the child was tested by the China-Wechsler Intelligence Scale for Children (C-WISC), and family function was assessed by the Family Environment Scale-Chinese Edition (FES-CV). Adult ADHD persistence was defined using DSM-IV criteria for ADHD, and academic outcome fell into two categories: higher academic level group (studying in senior middle school or above) and lower academic level group (studying in vocational secondary schools or below). Results: Stepwise multiple logistic regression analysis revealed that the father’s character, impulsive-hyperactive index as measured by the CPRS-48 and intellectual-cultural index as measured by the FES-CV independently predicted clinical outcomes in adults, with an AUC of 0.770 (P < 0.001, 95% CI = 0.678 to 0.863). The corresponding sensitivity and specificity were 0.743 and 0.727, respectively. The father’s education level, family economic level, and verbal IQ (VIQ) on the C-WISC independently predicted adult academic outcomes, with an AUC of 0.870 (P < 0.001, 95% CI = 0.796 to 0.944). The corresponding sensitivity and specificity were 0.813 and 0.783, respectively. Conclusion: Initial ADHD symptom severity and IQ, father’s character and education level, and family atmosphere and function affect adult clinical and academic outcomes. Addressing these areas early may help to improve the prognosis of ADHD into adulthood.